Etika Profesi dan Kepribadian Guru Madrasah - Syahbudin, Rizkan (JPT : Jurnal Pendidikan Tematik, 2020)
The teaching profession ethics is essentially the formulation and implementation of good teaching methods and their implementation in accordance with good attitudes and behaviors, both in school institutions and in the community where the teacher is located, however to make teaching as a profession still requires thinking which is broad and deep, considering also that the teaching profession is very decisive whether or not, the progress and decline of the development of future generations. Based on the above thought, this paper tries to present explanations about things that need to be considered in finding and determining the size that will be used in formulating professional teachers or teaching staff in accordance with the educational goals to be achieved, as well as guidance and suggestions for thinking that can be used as input for the learning process in educational institutions.